Effect and Mechanism of Si-Miao-Yong-An on Vasa Vasorum Remodeling in ApoE−/− Mice with Atherosclerosis Vulnerable Plague - Meng Li; Zhongwen Qi; Junping Zhang; Ke Zhu; Yueyao Wang (Frontiers Media S.A., 2021)
Objective: To observe the effect of Si-Miao-Yong-An (SMYA) on atherosclerosis (AS) vulnerable plaques, and to further explore the mechanism by vasa vasorum (VV) angiogenesis and maturation as an entry point.Methods: SPF-class healthy male ApoE−/− mice were randomized into model group, simvastatin group and SMYA group, and C57BL/6 mice were used as the control group. After 8 weeks of intervention, the pathological morphology of plaque was observed by HE staining; the VV density in plaque and aortic adventitia were observed by immunohistochemistry; VV maturation was measured by double-labelling immunofluorescence; the critical proteins of HIF-1α-Apelin/APJ and Ang-1/Tie signal pathways were detected by western blotting.Results: SMYA decreased the plaque area and the ratio of plaque to lumen area; increased the minimum thickness of fibrous cap and its effect was greater than simvastatin. SMYA suppressed the VV neovascularization; promoted smooth muscle cells recruitment and VV maturation, which maintained plaque stability; its effect was obviously superior to simvastatin. SMYA deceased the expression of HIF-1α, Apelin, APJ, Phospho-MEK1/2 (Ser217/221), Phospho-p44/42 MAPK (Erk1/2) (Thr202/Tyr204), Phospho-p70 S6 Kinase (Thr421/Ser424), Ang-2 and Tie-2; it also increased the expression of Ang-1, Phospho-Akt (Ser473), Phospho-FOXO1 (Ser256) and Survivin.Conclusions: SMYA can decrease the AS plaque area in ApoE−/− mice, suppress the VV neovascularization and promote the VV maturation, and stabilize AS vulnerable plaque. The mechanism could be regulating the HIF-1α-Apelin/APJ and Ang-1/Tie signal pathways.